Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE), 2017 2017
DOI: 10.23919/date.2017.7927243
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for run-time energy optimisation in many-core systems

Abstract: Abstract-In recent years, the focus of computing has moved away from performance-centric serial computation to energyefficient parallel computation. This necessitates run-time optimisation techniques to address the dynamic resource requirements of different applications on many-core architectures. In this paper, we report on intelligent run-time algorithms which have been experimentally validated for managing energy and application performance in many-core embedded system. The algorithms are underpinned by a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Learning Action Determination: There are various methods for determining the optimal action a t according to the state s t . In this paper, the well-known -greedy policy has been exploited, in which the dynamic policy is used for adjusting [36]. In -greedy policy, random action is selected from the actions set with the probability of , i.e., the best action is selected with the largest Q-value with the probability of 1 − .…”
Section: Solid Optimizationmentioning
confidence: 99%
“…Learning Action Determination: There are various methods for determining the optimal action a t according to the state s t . In this paper, the well-known -greedy policy has been exploited, in which the dynamic policy is used for adjusting [36]. In -greedy policy, random action is selected from the actions set with the probability of , i.e., the best action is selected with the largest Q-value with the probability of 1 − .…”
Section: Solid Optimizationmentioning
confidence: 99%
“…An online DVFS control strategy based on core-level modular reinforcement learning to adaptively select appropriate operating frequencies for each individual core was proposed in [60]. An Q-learning based algorithm was proposed in [61] to identify V/F pairs for predicted workloads and given application performance requirements. The study in [62] investigated imitation learning and reported higher quality policies in the context of dynamic VFI control in many core systems with different applications running concurrently.…”
Section: Reinforcement Learning (Rl)mentioning
confidence: 99%
“…Then, cover a number of approaches relying on reinforcement learning and supervised learning. In [18], reinforcement learning is applied through a cross-layer system approach to predict the best energy-performance trade-off in multicore embedded systems. It relies on a biologically-inspired runtime power management framework implementing a Q-learning algorithm, which selects the voltage-frequency levels to minimize energy consumption.…”
Section: Related Workmentioning
confidence: 99%